2015
DOI: 10.1172/jci79322
|View full text |Cite
|
Sign up to set email alerts
|

Proof-of-principle rapid noninvasive prenatal diagnosis of autosomal recessive founder mutations

Abstract: BACKGROUND.Noninvasive prenatal testing can be used to accurately detect chromosomal aneuploidies in circulating fetal DNA; however, the necessity of parental haplotype construction is a primary drawback to noninvasive prenatal diagnosis (NIPD) of monogenic disease. Family-specific haplotype assembly is essential for accurate diagnosis of minuscule amounts of circulating cell-free fetal DNA; however, current haplotyping techniques are too time-consuming and laborious to be carried out within the limited time c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…This haplotype-based approach has imposed two limitations to NIPT. First, it requires the elucidation of the maternal haplotype using a direct haplotyping approach (11)(12)(13), via pedigree analysis (8,14), or via founder haplotype analysis in selected populations (15). Second, this haplotype-based approach has limited the resolution in which the maternal inheritance of the fetus can be determined.…”
Section: Significancementioning
confidence: 99%
“…This haplotype-based approach has imposed two limitations to NIPT. First, it requires the elucidation of the maternal haplotype using a direct haplotyping approach (11)(12)(13), via pedigree analysis (8,14), or via founder haplotype analysis in selected populations (15). Second, this haplotype-based approach has limited the resolution in which the maternal inheritance of the fetus can be determined.…”
Section: Significancementioning
confidence: 99%
“…However, there have been few studies concerning detection of the maternal mutation. Recent work has demonstrated successful use of RHDO for detection of inheritance of maternal mutations . RHDO has been implemented successfully into some clinical laboratories, but generally remains prohibitively expensive .…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has demonstrated successful use of RHDO for detection of inheritance of maternal mutations. [26][27][28][29][30] RHDO has been implemented successfully into some clinical laboratories, but generally remains prohibitively expensive. 26 Importantly, most of RHDO requires a proband for haplotyping, meaning the test would not be available to a couple during their first pregnancy.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…In 2011, Peters et al () successfully identified a 4.2 M deletion on fetal chromosome 12 from cffDNA and proved that it is feasible to detect fetal sub‐chromosomal CNVs with the noninvasive method. Subsequently, between 2015 and 2017, a number of reports have demonstrated that fetal single‐gene disorders such as congenital adrenal hyperplasia, Duchenne muscular dystrophy, and type I Gaucher disease could also be identified via the noninvasive NGS approach (New et al, ; Xu et al, ; Zeevi et al, ).…”
Section: Introductionmentioning
confidence: 99%